Spatial distribution and characteristics of martial arts halls in China - Yao, Yunfeng; Liu, Shuangrui; Yu, Pengfei; Wu, Wanyi (Frontiers in Public Health, 2025)
IntroductionThe spatial distribution of martial arts halls plays a vital role in the inheritance and dissemination of Chinese Wushu culture. As important spaces for preserving martial arts traditions, these halls embody cultural continuity and serve as tangible carriers of intangible heritage. However, the nationwide spatial distribution characteristics and their underlying influencing factors remain insufficiently explored.MethodsUsing spatial geography techniques and data from 5,805 martial arts halls across China as of March 2025, this study employs kernel density estimation, spatial autocorrelation analysis, and regression models to examine the spatial distribution patterns and determinants of martial arts halls.ResultsThe results reveal significant regional disparities, with high concentrations in eastern provinces and sparse distributions in the west. The spatial structure is characterized as a “Four Core–Ring–Core Group–Double Belt” pattern. Population size, martial arts cultural heritage, policy support, and education level exert positive influences on hall distribution, whereas competition from the cultural and recreational industries poses challenges. Economic factors demonstrate a dual effect, acting both as a driver and constraint.DiscussionThe findings highlight that the spatial development of martial arts halls reflects broader socio-economic and cultural patterns in China. To enhance their sustainable development and promote balanced regional growth, policy interventions should strengthen cultural inheritance mechanisms, optimize resource allocation, and encourage integration between martial arts education and local development strategies.